2016
DOI: 10.1902/jop.2016.150447
|View full text |Cite
|
Sign up to set email alerts
|

Aloin Inhibits Interleukin (IL)‐1β−Stimulated IL‐8 Production in KB Cells

Abstract: Results indicated that IL-1β in saliva stimulates epithelial cells to produce IL-8 and that aloin effectively inhibits salivary IL-1β-induced IL-8 production by mitigating the p38 and ERK pathway. Therefore, aloin may be a good candidate for modulating oral inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 41 publications
(77 reference statements)
1
16
1
Order By: Relevance
“…Individuals having more missing teeth along with dental caries had elevated concentration of IL-1β. However, these findings contradict with another study,which reported that there was no significant difference of IL-1β in individuals with or without missing teeth or dental caries.Howsoever, this study shows that IL-1β value was significantly high in individuals with periodontitis and gingivitis and several studies support our results [38][39][40][41] . A cross-sectional study in adults (20-89 years) reported that IL-1β levels were significantly higher in participants with periodontitis (144pg/mL) compared to healthy participants (61pg/mL) 42 .…”
Section: Discussionsupporting
confidence: 85%
“…Individuals having more missing teeth along with dental caries had elevated concentration of IL-1β. However, these findings contradict with another study,which reported that there was no significant difference of IL-1β in individuals with or without missing teeth or dental caries.Howsoever, this study shows that IL-1β value was significantly high in individuals with periodontitis and gingivitis and several studies support our results [38][39][40][41] . A cross-sectional study in adults (20-89 years) reported that IL-1β levels were significantly higher in participants with periodontitis (144pg/mL) compared to healthy participants (61pg/mL) 42 .…”
Section: Discussionsupporting
confidence: 85%
“…IL‐1β plays an important role in the inflammatory host response in periodontal diseases, and has been suggested to be effectual target for the control of periodontitis . IL‐1β processing and secretion are tightly regulated by a two‐step mechanism .…”
Section: Discussionmentioning
confidence: 99%
“…Another study has shown that compounds of aloe species inhibit the production of pro-inflammatory cytokines and nitric oxide via inhibition of the MAPK signalling pathway [15]. More studies proved that treatment of aloin decreased the high production of interleukin (IL)-8 induced by IL-1β in KB cells, through the inhibition of activity of p38 and extracellular signal-regulated kinases pathway [19,29]. In recent years, more and more researchers have found that oxidative stress promotes the secondary injury after TBI, and among multiple factors, nicotinamide adenine dinucleotide phosphate oxidase (NOX) is critical in regulating the production of ROS [1].…”
Section: Introductionmentioning
confidence: 99%